CRIMES SOLVED THROUGH BITE MARKS - Maribondo de Lemos, Luciana (Health and Society, 2021)
The study is part of the area of ​​legal or forensic dentistry, which is a branch of Dentistry, specialized in helping the Judiciary Branch through the identification of marks and injuries caused by the dental arch, which is unique to each human being. The theme chosen for the research is relevant, as I identify with the subject and expand my professional knowledge. Aiming at the article, the description through a brief literature review, historical approach and the contribution of the Odontolegist's work in Post-Mortem. The realization of this work was based on research, such as: monographs, scientific articles and some research sites, such as Google. In its development, I show some cases where we have evidence and samples of human bites, their description and identification. It is concluded that the process of analysis of the Dentist is essential in the examinations of the body of crime and also in the knowledge of bite marks, charred bodies and all other elements that involve the oral cavity. This qualified professional works in favor of legal truth.